ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER (studi kasus pada PT. XL Axiata Tbk) - Sajow, Yunita Elshadai; Manoppo, W.S.; Keles, Dantje (Sam Ratulangi University, 2017)
The background in this study is to make the merger as one of the techniques for a company to survive in today's tight competition and also so that a company can strengthen its capital structure. The purpose of this study is to analyze whether there are differences in corporate financial performance before and after the merger based on financial ratios. Benefits in this study is as a source of corporate information on the financial performance of the company, so that later investors will be more appropriate in making investments.Company's financial performance is measured by using the financial statements consisting of income statement and balance sheet in the period 2012 to 2015, with data source namely secondary data obtained from Indonesia stock exchange in the period 2 years before the merger of 2012-2013 and 2 years after the merger 2014-2015. Comparison of financial ratio analysis is done by using several ratios, namely Profitability Ratio, Activity Ratio, Liquidity Ratio and Solvency Ratio. And also use data analysis techniques that is financial ratios.The results of the calculation of 8 financial ratios used, there are 6 financial ratios that decreased after the merger activities are Net Profit Margin, Gross Profit Margin, TurnOver Total Assets, Fixed Assets TurnOver, Debt Ratio and Debt To Equity Ratio. And 2 financial ratios of Current Ratio and Cash Ratio increased after conducting merger activity. It can be concluded that this company experienced a lot of decline in financial performance when conducting merger activity. As one of the suggestions, the company should review the cooperation or penggabunngan this business because based on the analysis of financial ratios, when companies merger financial performance decreased while the company is still standing alone or single financial performance is very good.Keywords: Financial Ratios, Financial Performance and Merger